Новые данные о фауне тлей (Homoptera, Aphidinea) Кавказа. Сообщение I - Мамонтова, В.А. (Вестник зоологии, 1982)
Microsiphum subalpica sp. n. Host -plant: Artemisia proceraL. Closely related to M.woroniecke J u d . (antennae and hair length,number of secondary rhinaria, habi- tat), differing from it by pigmentation,smaller body size, ratio of antennal segments, shape of siphunculi and cauda, number of caudal hairs (14). Type locality : Armenia, KadzharanPass, Litshk, 2300 m. Drepanisiphoniellaaceriscaucasica sp. n. Host-plant: Acer ibericum M.B cording to flask-shaped cauda,sixth antennal. segmentlength, ratio of apical proboscis segment to second segment of hind tarsus,it is close to the nomenotypic subspecies; alatae siphunculi shape andantennal hairs length are rather similar to sp. fugans. From both subspecies it clearly differs by pigmentation, unpowdered body, straight siphunculi in alatae, nolonger than ni apterae, sometimes shorter; length of theprocessusterminalisrea- ches 2/3 of third antennal segment; siphunculi i n apterae and a l a t e two times longer than second segment of hind-tarsus. T y p e locality: Armenia, Garni. Stomaphiscupressi caucasica"ssp. n. Host-plant : Cupressus sempervireus. The most interesting peculiarityis thatantennal segmentslength ratio in Caucasian alatae (described for the first time) agreed with sp. cupressi apterae from Kenya; at the same time apterae of both subspeciesare clearly distinct by this character. Thenew subspecies also differs by body (ca. 0.1 m m and antennal (ca. 0.064 mm) hair length, by length of sixth antennal segment processus terminalis, by number of secondary rhinaria (17-20 over the whole thirdantennal segment versus nine over distal part in Kenyan), andby button-like end of sixth antennalsegment processus terminalis. T y p e l o c a l i t y : Abkhazia, Gudauta.